Compassion Fatigue and Burnout: What Managers Should Know. Issue 4 (October 2020) - Slatten, Lise Anne; Carson, Kerry David; Carson, Paula Phillips
Abstract : Most health care employees experience and are bolstered by compassion satisfaction as they deal with patients in need. However, the more empathetic a health care provider is, the more likely he or she will experience compassion fatigue. Compassion fatigue is a negative syndrome that occurs when dealing with the traumatic experiences of patients, and examples of symptoms include intrusive thoughts, sleeping problems, and depression. Compassion fatigue is different from burnout. Compassion fatigue is a rapidly occurring disorder for primary health care workers who work with suffering patients, whereas burnout, a larger construct, is a slowly progressing disorder for employees who typically are working in burdensome organizational environments. Managers can mitigate problems associated with compassion fatigue with a number of interventions including patient reassignments, formal mentoring programs, employee training, and a compassionate organizational culture. With burnout, health care managers will want to focus primarily on chronic organizational problems.